The Utility Extent of Linguistics to Language Teaching: An Experimental Evaluation - Md. Faruquzzaman Akan; Hassan Mahill Abdallah Hassan; A B M Shafiqul Islam; Abdelrahman Elyass Mohamed Abdelmajd (Journal of English Language Teaching and Linguistics, 2017)
To approach the very questions how and how far linguistics helps language teaching, we have to examine, analyze and evaluate them critically from various view-points. During the Second World War, the importance of linguistics in language teaching was noticed forthwith for the first time. Linguistics and language teaching have the same subject matter to deal with. Though linguistics is the scientific study of language, it has some specific role to play in the process of language teaching from the earlier to the modern times. Stephen Pit Corder (1975:143) says, “… the relevance of theoretical linguistics to language teaching is indirect and it is not the task of a theoretical linguist to say what relevance it may have. This is the field of applied linguistics.” According to the American linguist Noam Chomsky and some others, applied linguistics has a direct relationship with language teaching which is a pragmatic process and cannot take place in a total isolation. It takes help from various related sources and fields such as general, educational and social psychology; sociology, social anthropology and so on. Here, linguistics provides a language teacher with effective tools. However, as Dwight Bollinger says (1975a:22), “Language teaching is not linguistics, any more than medicine is chemistry….” So, the aim of this paper is to show the role of linguistics in teaching both foreign languages and any first languages or mother tongues.